2016
DOI: 10.1039/c6fd00037a
|View full text |Cite
|
Sign up to set email alerts
|

Design of artificial membrane transporters from gold nanoparticles with controllable hydrophobicity

Abstract: Gold nanoparticles with variable hydrophobicity have been prepared in three different size regimes following established methods. The control of hydrophobicity was achieved by complexation of the 18-crown-6-CH-thiolate ligand shell with potassium ions. Potassium dependent phase transfer of these particles from dispersion in water to chloroform was demonstrated, and the equilibrium partitioning of the particles in water-chloroform liquid/liquid systems was quantified by optical spectroscopy. The gradual complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The fluorescence intensity of safranin O was calibrated against the membrane potential values calculated from the Nernst equation ( Figure S2 ). 20 , 23 If, instead of valinomycin, the nanoparticles are added, a rapid polarization of the membrane in the same direction (inside negative) is also observed, but the final value does not depend on the potassium concentrations on both sides of the membrane but only on the amount of nanoparticles added.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence intensity of safranin O was calibrated against the membrane potential values calculated from the Nernst equation ( Figure S2 ). 20 , 23 If, instead of valinomycin, the nanoparticles are added, a rapid polarization of the membrane in the same direction (inside negative) is also observed, but the final value does not depend on the potassium concentrations on both sides of the membrane but only on the amount of nanoparticles added.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that the use of thiolated crown ethers (18‐C‐6‐CH 2 ‐SH) as capping agents for gold nanoparticles allowed us to control the hydrophilicity via complexation of K + cations to the crown ether, resulting in phase transfer between aqueous and organic solvents . Here we demonstrate that this ligand can also be used to prepare thermoresponsive particles that show entropy driven reversible agglomeration with controllable transition temperatures directly related to the degree of cation complexation of the crown ether moiety (Scheme ).…”
Section: Methodsmentioning
confidence: 79%
“…40 nm in size and to modulate their dispersibility and phase transfer between water and oil. [28][29][30][31][32][33][34][35] When shaking the emulsion, the chloroform sublayers immediately adopted a reddish brown (4 nm GNPs) or pink (7 nm GNPs) color, which we attribute to the transfer of some GNPs to the chloroform phase (see Fig. ESI1 †).…”
Section: Resultsmentioning
confidence: 91%
“…We have previously reported the transfer of a number of different GNPs across phospholipid mono-and bilayer membranes and also noted their ability to carry across ionic charge. [35][36][37][38] Drawing on this experience, we have conducted an electrochemical experiment that independently conrms barium ion transport across such a hydrophobic boundary between two aqueous compartments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation